2015
DOI: 10.1007/s12035-015-9274-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polymorphism of Neuronal Nitric Oxide Synthase Gene with Risk to Parkinson’s Disease

Abstract: Environmental factors are implicated in aging as well as genetic predisposition-induced Parkinson's disease (PD) pathogenesis. Wrongdoers increase oxidative stress and nitrosative burden, which eventually degenerate the nigrostriatal dopaminergic neurons. Inhibition of the expression of nitric oxide synthase (NOS), an enzyme responsible for nitric oxide (NO) biosynthesis, prevents the demise of the nigrostriatal dopaminergic neurons. Polymorphism of NOS is thus expected to alter PD susceptibility. The study th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…In this meta-analysis, we enrolled 4 articles [ 1 , 3 , 23 , 44 ] including 789 cases and 1369 controls to investigate the role of NOS1 exon18 polymorphism in Parkinson's disease. The result was shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this meta-analysis, we enrolled 4 articles [ 1 , 3 , 23 , 44 ] including 789 cases and 1369 controls to investigate the role of NOS1 exon18 polymorphism in Parkinson's disease. The result was shown in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In this retrospective analysis, 5 studies [ 1 , 3 , 23 , 44 , 45 ] involving 1246 cases and 1606 controls were included to explore the link between NOS1 exon29 polymorphism and PD. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, familial aggregation and co-aggregation of Parkinson's disease have indicated that genetic factors also play an important role in the development of Parkinson's disease. Previous studies have shown that genes encoding b-site APP cleaving enzyme 1, myeloid cells 2, cyclooxygenase-2, aldehyde dehydrogenase 2, neuronal nitric oxide synthase, and bone marrow stromal cell antigen 1, all contribute to the development of this disease (Dai et al, 2015;Goudarzian et al, 2015;Gupta et al, 2015;Wang et al, 2015a,b;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%